Occupational employment projections to 2014. - Hecker, Daniel E. (Monthly Labor Review, 2005)
This article reports that employment in professional and related occupations and in service occupations in the U.S. is expected to increase the fastest of all occupations and add the most jobs from 2004 to 2014. Large numbers of jobs in community and social services are in the government sector, and even though jobs in that sector will be growing slowly, they will nevertheless account for one-sixth of all new jobs. Employment of office and administrative support occupations should grow a bit more slowly than overall employment in almost all industries, due to both continued office automation, including that related to electronic business, and the greater use that organizations make of temporary workers employed by the employment services industry. Employment in these occupations is projected to decline by 13,000 jobs, with self-employment accounting for 8.1 percent of the drop. Employment of veterinary technologists and technicians, classified as a health care occupation, is projected to grow rapidly as pet owners spend more on advanced animal care services, such as preventive denial care and surgical procedures, and as employers replace veterinary assistants with these more highly skilled workers. Legislation and court rulings setting standards in occupational safety and health, equal employment opportunity, wages, health care, pensions, and family leave will increase demand for employment, recruitment, and placement specialists.